A stability-indicating high performance liquid chromatography method to determine apocynin in nanoparticles - Juliana Kovalczuk de Oliveira; Débora Fernanda Veres Ronik; Jociani Ascari; Rubiana Mara Mainardes; Najeh Maissar Khalil (Elsevier, 2017)
In this study, we developed and validated a fast, specific, sensitive, precise and stability-indicating high performance liquid chromatography (HPLC) method to determine the drug apocynin in bovine serum albumin (BSA) nanoparticles. Chromatographic analyses were performed on an RP C18 column and using a photodiode array detector at a wavelength of 276 nm. Mobile phase consisted of a mixture of acetonitrile and 1% acetic acid (60:40, v/v), and it was eluted isocratically at a flow rate of 0.8 mL/min. The retention time of apocynin chromatographic peak was 1.65 min. The method was linear, precise, accurate and specific in the range of 5-100 μg/mL. The intra- and inter-day precisions presented relative standard deviation (RSD) values lower than 2%. The method was robust regarding changes in mobile phase proportion, but not for flow rate. Limits of detection and quantitation were 78 ng/mL and 238 ng/mL, respectively. Apocynin was exposed to acid and alkali hydrolysis, oxidation and visible light. The drug suffered mild degradation under acid and oxidation conditions and great degradation under alkali conditions. Light exposure did not degrade the drug. The method was successfully applied to determine the encapsulation efficiency of apocynin in BSA nanoparticles.